Teaching OCL Standard Library: First Part of an OCL 2.x Course - Chimiak-Opoka, Joanna; Demuth, Birgit (Electronic Communications of the EASST, 2011)
Our aim is to provide a complete set of materials to teach OCL. Theycan be used in bachelor or master programs of computer science curricula and fortraining in an industrial context. In this paper we present the first part of the courserelated to the OCL Standard Library. This part provides model independent examplesto teach OCL types and their operations. It enables users to gain a basicunderstanding of the OCL Standard Library, which can be used as a starting pointto write model constraints (OCL specifications) or model queries. Additionally, tothe content of the paper, we provide a set of OCL packages, exercise proposals andlecture slides.